PHYSIOLOGICAL REACTION OF PLANTS OF FAGOPYRUM ESCULENTUM MOENCH BUCKWHEAT VARIETIES UNDER DIFFERENT HYDROPRIMING REGIMES IN THE EARLY STAGES OF ONTOGENESIS - Liashenko, V.; Sakhno, T.; Tryhub, O.; Semenov, A. (Scientific Progress & Innovations, 2022)
In modern conditions of the need to increase the volume of agricultural production, it may be appropriate to use priming technologies to prepare seed for sowing. We studied the physiological reactions of plants of buckwheat cultivars Fagopyrum esculentum Moench under different regimes of hydropryming in the early stages of ontogenesis. We have studied the physiological responses of Fagopyrum esculentum Moench buckwheat cultivars under various hydropickling regimes at the early stages of ontogenesis. The electrical conductivity of buckwheat seeds was determined by the release of electrolytes into solution during 2–24 h of seed hydration at a temperature of 20°C using an AD8000 ADWA multimeter. Laboratory experiments were performed in three biological and five analytical replicates. In a laboratory experiment, vigour was assessed on day 3 and germination on day 7. Data were processed by conventional statistical methods of analysis. The data were processed by generally accepted statistical methods of analysis. It was found that the buckwheat varieties Rozhevokvita 2-19 and P-454 increased the electrical conductivity of seed exudates in 300 minutes by 52 and 78 % respectively. During priming, the seed growth energy is maximally increased by 46 % for the Rozevokvita 2-19 variety after 24 hours, and by 70 % for the P-454 variety after 10 hours of priming. It was found that for varieties with low growth vigour Rozhevokvita 219 and R-454, hydro-priming increased the energy for 10 hours of seeding by 3.5 and 6 times, respectively. With regard to the buckwheat variety P-338, it is advisable to note the reduction of vigour after priming by almost 40 %. The obtained results reveal some aspects of the mechanism of interaction of hydropryming with plant objects, which allow more reasonable use of hydropryming regimes for growing different varieties of buckwheat.